Septated concha bullosa in an antrochoanal polyp patient - Ertugrul, Suha (International Journal of Research in Medical Sciences, 2017)
The term of septated concha bullosa has been described recently and it is an uncommon pneumatization anomaly of the middle turbinate. Solitary, benign soft tissue masses originating at the maxillary sinus and extending to the nasopharynx are called antrochoanal polyps. Antrochoanal polyp may be accompanied by concha bullosa. However, combination of septated concha bullosa and antrochoanal polyp has never been reported to the best of our knowledge. This paper presents a 45-year-old male patient who has a combination of septated concha bullosa and antrochoanal polyp.